Effect of Accounting Income And Taxable Income on Earnings Persistance on Miscellaneous Industry Sector Registered in Indonesia Stock Exchange 2015-2019 - NANDA SURYADI; Riri Mayliza; Ratna Nurani; Arie Yusnelly (Asosiasi Dosen Akuntansi Indonesia, 2021)
Earnings persistence is an indicator to evaluate expected future accounting income implemented in current year earnings. Persistent earnings indicates a profit which does not experience fluctuation frequently on each of its period and has stabile tendency. The objective of this research was to collect empirical proof of the effects of permanent differences, temporary differences, large positive book-tax differences, and large negative book-tax differences on Earnings Persistence. Population involved in the current research was Manufacture Companies in Miscellaneous Industry Sector registered in Indonesia Stock Exchange in 2015-2019. Among population involved, 11 companies were chosen as research sample through purposive sampling method. Hypothesis raised, in this case, was tested using panel data regression. Research results indicated that permanent differences significantly affected earnings persistence. Meanwhile, other results obtained that temporary differences, large positive book-tax, and large negative book-tax did not affect earnings persistence. Simultaneous test further confirmed that permanent difference, temporary differences, large positive book-tax differences, and large negative book-tax differences affected earnings persistence simultaneously.